An Investigation into the Factors Influencing Unethical Consumer Behavior in Selangor - Nazahah, Abd. Rahim (2009)
This study investigates consumers' motivation for behaving unethically and to understand the factors influencing it. As there are less research and reports on factors influencing the unethical consumer behaviors in Malaysia, thus study on this issue is important. Respondents from Selangor, which is from one of the states in Malaysia was chosen as the sample for this study. A purposive sampling technique was implemented in selecting the respondents aged between 19 to 35 years old. The Theory of Planned Behavior (TPB) model is applied to reveal the secret behind it. It is found that the potential factors of consumers behaving unethically are attitude, subjective norms, perceived behavioral control and habit. Given the complexity of this integrated model and simultaneous involvement of many factors, the SEM is used and a multivariate analysis technique is adopted. It shows that the revised model for Selangor consumers produced no significant direct impact. It is also identified that those factors; attitude, subjective norms, perceived behavioral control and habit are insignificant to the relationship between those factors and the intention to behave unethically. It is found for the sample that there are mediating effects of intention in two relationships; intention mediates the relationship between subjective norms and behavior and intention mediates the relationship between habit and behavior.